The effect of fatigue and body mass index on dynamic balance - Che, Xiaohui (2019)
Context: Poor dynamic balance is associated with lower limb injury. While studies have shown that both neuromuscular fatigue and body mass index (BMI) negatively affect dynamic balance, few have investigated their interaction. Purpose: The purpose of this study is to investigate the effect of fatigue and BMI on dynamic balance in athletes. It was hypothesised that fatigue would negative affect dynamic balance and this effect was further amplified by higher BMI. Method: 2x2 mixed model design was used. 9 athletes from intermittent sports with high BMI and 9 with normal BMI were recruited. Participants underwent a fatigue protocol which include jogging, push-ups, step-ups, sit-ups and sprinting. Postural control was measured using the Y-balance test before and after the fatigue protocol. 2D video analysis was performed to analyse knee and hip flexion angles. Borg’s scale of Rating of Perceived Exertion was used to monitor fatigue levels. Composite Y-balance test scores, normalized reach scores in each direction as well as the joint angles was used for data analysis. Results: for Y-balance Test scores, significant within-group difference was found in the composite (p=0.011) score as well as normalized reach distance in anterior (p=0.005) and posterolateral direction (p=0.015). For joint angles, a significant difference was found in the posterolateral hip flexion angle between groups (p=0.042). No significant group by time interaction was found in Y-balance test scores and joint angles. Conclusion: Fatigue negatively affects dynamic postural control, particularly in the anterior and posterolateral direction, and this effect is not influenced by BMI.